2015
DOI: 10.1134/s1028334x15030204
|View full text |Cite
|
Sign up to set email alerts
|

Field studies and some results of numerical modeling of a ring structure on Baikal ice

Abstract: Geological ring structures of various sizes and ori gins are observed on the Earth's surface. In the past decade, ice ring structures on Lake Baikal were regu larly identified by satellites [1]. On April 4, 2009, these structures emerged in the western end of South Baikal and near the Svyatoi Nos Peninsula in Central Baikal [1][2][3] and were destroyed along with the ice at the end of April. The expedition for studying the ice and hydrophysical measurements in the area of the ring structure in South Baikal was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 5 publications
5
21
0
1
Order By: Relevance
“…However for the conductivity/salinity this similarity is only partial. Granin et al () found less mineralised water in the center than at the periphery of the ring (this is similar to our observations), but from the depth of 40 m downward their observations show no increase of salinity. This observation apparently led the authors to conclude that this anomalous structure results from upwelling of deep waters (with lower mineralisation and higher temperature) through the thermocline, and is potentially related to the presence of gas hydrates in bottom sediments.…”
Section: Hydrological Structure Beneath the Ice Ringssupporting
confidence: 92%
See 2 more Smart Citations
“…However for the conductivity/salinity this similarity is only partial. Granin et al () found less mineralised water in the center than at the periphery of the ring (this is similar to our observations), but from the depth of 40 m downward their observations show no increase of salinity. This observation apparently led the authors to conclude that this anomalous structure results from upwelling of deep waters (with lower mineralisation and higher temperature) through the thermocline, and is potentially related to the presence of gas hydrates in bottom sediments.…”
Section: Hydrological Structure Beneath the Ice Ringssupporting
confidence: 92%
“…Our observations for Lake Baikal in 2012 and 2014 show water structure similar to the one found below the ice ring in 2009 (Granin et al ) for temperature (core values 1–1.25°C). However for the conductivity/salinity this similarity is only partial.…”
Section: Hydrological Structure Beneath the Ice Ringssupporting
confidence: 86%
See 1 more Smart Citation
“…It is not possible to estimate the driving force of eddy generation without in situ data before the formation of the ice ring in Southern Baikal in 2009 or near Cape Krestovskiy in 2013. However, for the region of the Nizhneye Izgolovye Cape, there are several cases that appear to contradict the hypothesis of upwelling of deep water (Granin et al ) and the results of estimation of period for the formation of the ring structure (Granin et al ).…”
Section: Discussionmentioning
confidence: 98%
“…Granin et al () have analyzed heat fluxes in the ice cover and in the system water–ice. They calculated variations in the ice thickness inside the ring in Southern Baikal in 2009 in the framework of the Stefan problem using a two‐dimensional axis‐symmetrical model and current speed from a 3D nonhydrostatic model (using the upwelling of deep water hypothesis).…”
Section: Discussionmentioning
confidence: 99%